Circular RNAs Sparkle in the Diagnosis and Theranostics of Hepatocellular Carcinoma - Wang, Menglan; Wu, Minjie; Xie, Tian; Chen, Jianxiang (Frontiers in Genetics, 2021)
Abstract Exonic circular RNAs (circRNAs) are a novel subgroup of noncoding RNAs, which are generated by a back-splicing mechanism of the exons or introns. Unlike the linear RNA, circRNA forms a covalently closed loop, and it normally appears more abundance than the linear products of its host gene. Due to the relatively high specificity and stability of circular RNAs in tissues and body fluid, the circular RNAs have attracted widely scientific interest for its potential application in cancer diagnosis and the guide for preclinical therapy, especially for hard to treat cancers with high heterogeneity, such as hepatocellular carcinoma (HCC). Thus, we summarize the updated knowledge of circular RNAs, including the mechanism of the generation endogenous circular RNAs, their regulatory, diagnostic and therapeutic roles in HCC.